Survei Sarana dan Prasarana Olahraga Tarung Drajat di Satuan Latihan Diklat Kota Kupang - Ilang, Hendrikus; M. Boleng, Lukas; Dwi. A. Fufu, Ronald Dwi. A. Fufu (Nusa Cendana University, 2024)
Problems that are examined: With the facilities and infrastructure of the Tarung Derajat Sports trainers, this makes it a consideration for evaluating Tarung Derajat Training to the next stage, from the trainer's side it is possible to carry out training using the facilities and infrastructure. Therefore, the standardization of sports facilities and infrastructure used to concentrate the Tarung Derajat Training Unit in Kupang City has so far used the KONI NTT Youth Sports building, which has stalled in construction and must be brought into line with National Standards. The Kupang City Derajat Tarung Training Unit does not yet have the facilities and infrastructure that are officially owned by this sport, so it is necessary to reconsider the availability of these facilities and infrastructure. Based on the background description above, the researcher is interested in conducting research on